A New Fault Slip Mode Unveiled in the Regional Dynamic Triggering of the 2023 Turkey Kahramanmaraş Earthquake Sequence - Luo, Heng; Zhou, Yijian; Zhao, Zeyan; Koekuem, Mehmet; Wang, Teng; Yue, Han; Buergmann, Roland (Amer Geophysical Union, 2025)
Faults can slip at vastly different rates, generating both high-stress-drop regular earthquakes and low-stress-drop slow slip events (SSEs). Here, we document a transitional mode of high-stress-drop but silent slip with two Mw >= $\mathit{\ge }$ 5 events that were triggered by the 2023 Turkey Kahramanmara & scedil; earthquake sequence. Specifically, we identify eight fault slip events from radar interferometry, none of which are reported in seismic catalogs. Except for four typical aseismic creep events, two events represent earthquakes whose waveforms were obscured within the coda waves of the mainshocks. Notably, we find two silent events that did not radiate discernible high-frequency seismic energy nor produce local aftershocks but did exhibit high stress drops of 4-6 MPa, similar to regular earthquakes. These two silent events likely represent a new fault slip mode positioned between regular earthquakes and SSEs. The identification of these diverse shallow slip events, which are missed in seismic catalogs, calls for reevaluation of faulting mechanisms, the nature of static/dynamic triggering effects, and seismic hazard assessments.
Keywords: InSAR; earthquake; slow slip event; dynamic triggering; stress drop